Perancangan User Experience Website Yayasan Ihyaul Quran Indonesia menggunakan Metode Human Centered Design - Mohammad Royhan Afif Al Mudhari; Hanifah Muslimah Az-Zahra; Khalid Rahman (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Ihyaul Quran Indonesia Foundation is a foundation engaged in Al-Quran education. An official foundation needs a website as public information and to support the programs of the foundation. According to the results of initial interviews conducted with foundation stakeholders, the foundation needs a website that functions as a funnel for information on the foundation for the public and to support for making donations. However, the requirement continues to increase as this research progresses. There are two groups of users of this website, namely the general public and administrators who manage the website. This research uses the Human Centered Design (HCD) method which is user-oriented with the hope that the design made is truly in accordance with the user's needs. The HCD method begins with the process of understanding and specifying the context of use that will produce personas, analysis of the system environment, and system objectives. The second stage is to analyze user requirements that generate functional and non-functional requirements along with use cases. The third stage is to design a solution that produces a wireframe and high fidelity prototype. The last stage is an evaluation of the solution design. The results of the evaluation using the System Usability Scale (SUS) got a score of 87 in the general public user group design, 78.75 in the admin user group design, which means it has adjective ratings of excellent. Evaluation using the User Experience Questionnaire (UEQ) got an excellent score on the attractiveness, efficiency, dependability, and simulation aspects. While the aspects of perspicuity and novelity got good scores.